The Unspoken in the Speech of Symbolism School - Mohammed, Basheer Thabit; Al-Ghariri, Lateef Mahmoud Mohammed (Arab Journal for Sciences and Research Publishing, 2021)
It required the literary man to base his artistic output on a basic basis from which to achieve literary creativity, and literary trends and currents have varied, specifically in the postmodern period, which directed its attention to margins and the casual things. Accordingly, we will try to discover and search for what was rejected and excluded by the literary schools, while symbolism school was interested in and considered it as an original and a reference for them. There are some technical procedures that symbolism adopted and applied that were excluded and marginalized before, as it constitutes for them aesthetic values, literary pleasure and a special emotional pleasure. Therefore, we find that they relied on music and the mysterious feelings it evokes in the mind that are difficult to express in ordinary language. They (Symbolism school) found a new kind of authority to write the poetry, specifically after feeling freedom and openness to unlimited horizons.
Keywords: Unspoken; Sensory messaging; Musical composition; Icon; Speech; Marginal